2006
DOI: 10.1007/s00259-006-0094-6
|View full text |Cite
|
Sign up to set email alerts
|

Robustness of estimation of differential renal function in infants and children with unilateral prenatal diagnosis of a hydronephrotic kidney on dynamic renography: How real is the supranormal kidney?

Abstract: The current study supports the existence of age-related variation in the disparity of DRF estimations using the AUC and Rutland/Patlak methods in children with unilateral pelvic dilatation. The close agreement between the AUC and Rutland/Patlak techniques in estimation of DRF in older children supports their use. However, careful quality control of the renogram analysis is essential in young babies. Supranormal renal function (>55% DRF) may in fact be much less common in this group of children than is currentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
11
1
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 13 publications
5
11
1
2
Order By: Relevance
“…However, even with cortical imaging where, in comparison to diuretic renography, no complex processing is involved and image statistics are superior to dynamic renography, high values of SD of up to 3.9% were found. When these data are, wherever conceptually possible, compared with our work [12,13,16], we can conclude that our results are comparable (Table 1) and that the observed variation in DRF estimation belongs to the same order of magnitude.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…However, even with cortical imaging where, in comparison to diuretic renography, no complex processing is involved and image statistics are superior to dynamic renography, high values of SD of up to 3.9% were found. When these data are, wherever conceptually possible, compared with our work [12,13,16], we can conclude that our results are comparable (Table 1) and that the observed variation in DRF estimation belongs to the same order of magnitude.…”
Section: Discussionsupporting
confidence: 86%
“…In an older study comparing 131 I-OIH (ortho-iodohippurate) renography with 99m Tc-DMSA (dimercaptosuccinic acid) cortical scintigraphy in 100 patients, the SD of differences of paired measurements was 3.94 and 4.27% for a single posterior view and geometric mean 99m Tc-DMSA uptake, respectively [15]. The latest study [16] has also compared two methods of DRF calculation (integral and PatlakRutland) in a large number of pediatric patients: data were processed by one observer and SD of differences of repeated measurements was 3.9%. This is also the only work found in the literature investigating the effect of patient age on DRF variability: a significant difference between age groups of below and above 1 year of age was found, but the observed variable was the number of patient studies with difference between DRF calculation methods greater than 5%.…”
Section: Discussionmentioning
confidence: 97%
“…In spite of these observations between the MAG-3 and DMSA RRF estimations [4,5], some problems also exist in children with unilateral hydronephrosis, such as supranormal RRF estimations and methodological considerations [3,6]. In our study, a disagreement was revealed only in a limited number of cases with a difference of C5% between RRF estimations or supranormal functions (Tables 1, 4).…”
Section: Discussioncontrasting
confidence: 72%
“…In a study by Ö zcan et al [3], the robustness of RRF estimations derived from diuretic renography in children with unilateral hydronephrosis has been evaluated using the correlation between two methods of MAG-3 RRF calculation, namely, area under the curve and Patlak methods, without a reference method such as DMSA scan. Our results showed that the repeated measures of RRF of MAG-3 and DMSA were correlated for both time intervals and for both observers.…”
Section: Discussionmentioning
confidence: 99%
“…The differences reported in the literature between the AUC and RP plot methods are small, about 1% [5], and the reproducibility of both methods is good, between 1.7 and 2.2% for the AUC method and about 2.8% for the RP plot in adults and children with normal renal function and no gross asymmetry of DRF or a solitary kidney [6,7]. The studies also suggest that reproducibility is reduced in very young children and in patients with poor renal function [5,8,9].…”
Section: Introductionmentioning
confidence: 83%